2016
DOI: 10.7600/jpfsm.5.57
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute exercise on executive function in children with and without neurodevelopmental disorders

Abstract: An increasing number of studies have examined the effects of acute aerobic exercise on executive function (i.e., higher-order cognitive abilities involved in goal-directed behaviors) in healthy children. More recently, studies have begun to extend these empirical findings to children with neurodevelopmental disorders such as attention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorder (ASD). Here, we review what is known about the effects of acute exercise on executive function in children with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
2
3
0
Order By: Relevance
“…With sufficient statistical power, this study supported that acute exercise might demonstrate greater effects on the sustained attention and discrimination ability in children with LD than TD children. The results are consistent with the previous literature regarding the effects of physical exercise on the attentionrelated symptoms of children with different disabilities (Piepmeier et al, 2015;Soga et al, 2016;Vogt, Schneider, Abeln, Anneken, & Strüder, 2012). Given that children with LD are likely to be associated with cognitive dysfunction, they may gain greater cognitive benefits from the acute exercise than TD children because the effects induced by the exercise would distinctly compensate for the deficit in EF (Cook et al, 2015;Heller et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…With sufficient statistical power, this study supported that acute exercise might demonstrate greater effects on the sustained attention and discrimination ability in children with LD than TD children. The results are consistent with the previous literature regarding the effects of physical exercise on the attentionrelated symptoms of children with different disabilities (Piepmeier et al, 2015;Soga et al, 2016;Vogt, Schneider, Abeln, Anneken, & Strüder, 2012). Given that children with LD are likely to be associated with cognitive dysfunction, they may gain greater cognitive benefits from the acute exercise than TD children because the effects induced by the exercise would distinctly compensate for the deficit in EF (Cook et al, 2015;Heller et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…In particular, the effects of a single bout of exercise have raised researchers' attention. A meta-analytic review has indicated that engaging in acute exercise could help children with neurodevelopmental disorders (e.g., intellectual and developmental disorders) enhance their EF performance, including areas such as inhibitory control, working memory, and cognitive flexibility (Soga, Kamijo, & Masaki, 2016). For TD children, previous studies have revealed that acute exercise shows beneficial effects on vitality, reduced impulsivity, behavioral inhibition, cognitive development, and EF (Chang, Labban, Gapin, & Etnier, 2012;Palmer, Miller, & Robinson, 2013;Piepmeier et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Mcmorris et al [42] reported that acute, intermediate-intensity exercises have a strong beneficial effect on the speed of response in the WM tasks in adults. Moreover, the result is similar to those of studies investigating the effect of acute exercises on the executive function in normal children [43].…”
Section: Discussionsupporting
confidence: 86%
“…Other possible moderating factors such as improved motor skills[46] (needed in many neurocognitive tasks) or motivational aspects, may play a role as well in the relationship between sports participation and neurocognitive functioning.…”
Section: Discussionmentioning
confidence: 99%